Power quality enhancement of unbalanced Distributed-Resources based on triple-loop compensation - Omar Mohamed Salim; Amgad El-Sayed Salem Aboraya (Ain Shams Engineering Journal, 2024)
Distributed generation (DG) allows the microgrid (MG) to be more active and flexible. However, MG is exposed to some power quality (PQ) issues such as harmonics and voltage sag/swell especially during unbalanced loading. To overcome these challenges, isolated areas adopting DG technology rely on ensuring an active compensation of PQ on each standalone micro-source. This paper addressed a control strategy for a specific implementation named 3P four-leg inverters (3P4LI). This implementation is based on DG connection to improve the output voltage regulation, total harmonic distortion (THD) and unbalanced load under various load types. A new control architecture named triple-loop compensation (TLC) based on PI, PR, and feedforward schemes, is proposed. Proposed TLC parameters are optimized based on a multi-objective function under the constraints to compensate for the voltage regulation, THD mitigation, system stability, and unbalanced load compensation to meet the recommended standards. The proposed strategy has proven that the system voltage has been regulated successfully for both 3P/1P loads with minimum error. The voltage unbalanced factor (VUF) has been successfully minimized during aggressive loading. The TLC performance has met the objectives ensuring 5–6 times enhanced accuracy compared to the previous work.